2010
DOI: 10.1021/pr100643m
|View full text |Cite|
|
Sign up to set email alerts
|

Caterpillar- and Salivary-Specific Modification of Plant Proteins

Abstract: Though there is overlap, plant responses to caterpillar herbivory show distinct variations from mechanical wounding. In particular, effectors in caterpillar oral secretions modify wound-associated plant responses. Previous studies have focused on transcriptional and protein abundance differences in response to caterpillar herbivory. This study investigated Spodoptera exigua caterpillar-specific post-translational modification of Arabidopsis thaliana soluble leaf proteins by liquid chromatography/electrospray i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 96 publications
0
30
0
2
Order By: Relevance
“…The Bede laboratory has been investigating the effect of saliva from larval S. exigua on modification of host proteins, and found that saliva is responsible for the cysteine oxidation of Rubisco and other proteins [46], which is not surprising considering the relatively high level of GOX in this insect [47]. Perhaps more intriguing were changes in the phosphorylation patterns of host proteins when dephosphorylation of a chaperonin at the Thr 59 and lipoxygenase 2 at Ser 600 occurred [46]. The effects of phosphorylation or oxidation on protein activity were not reported in this study, but the results with lipoxygenase 2 are particularly interesting because of its role in JA biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The Bede laboratory has been investigating the effect of saliva from larval S. exigua on modification of host proteins, and found that saliva is responsible for the cysteine oxidation of Rubisco and other proteins [46], which is not surprising considering the relatively high level of GOX in this insect [47]. Perhaps more intriguing were changes in the phosphorylation patterns of host proteins when dephosphorylation of a chaperonin at the Thr 59 and lipoxygenase 2 at Ser 600 occurred [46]. The effects of phosphorylation or oxidation on protein activity were not reported in this study, but the results with lipoxygenase 2 are particularly interesting because of its role in JA biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that these findings reflect an intricate prioritization of plant responses to prevailing and anticipated challenges, according to their expected harshness and cumulative long-term costs. Herbivore saliva was suggested to enable plants to differentiate between herbivory and physical damage (Korth and Dixon 1997;Thivierge et al 2010); however, the correlation between present and future herbivory might be rather limited (Karban and Adler 1996), reducing the predictive value of salivary cues. On the other hand, prevailing competition and nutrient deficiency often present severe stresses, which are highly autocorrelated with continued stress.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, plastic responses to herbivory can be elicited by two sources of information-(a) biomass loss and mechanical injury, which typically generate both direct damages and resource-level cues (sensu Aphalo and Ballare 1995) and (b) salivary cues, which are considered pure cues and were suggested to be used by plants to differentiate herbivory from other mechanical damages (Korth and Dixon 1997;Thivierge et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic investigations provided further evidence of the vulnerability of the CO 2 fixing process to insect attack by showing that herbivory, or even the application of the insect´s saliva, also reduced the abundance of Rubisco activase (RCA) in Nicotiana attenuata and Arabidopsis (Giri et al, 2006;Thivierge et al, 2010). RCA is a key regulatory enzyme of photosynthetic carbon assimilation that modulates the activity of Rubisco by facilitating the removal of inhibiting sugar phosphates from its active site (Portis, 1995).…”
Section: Main Photosynthetic Genes Targeted By Biotic Stressmentioning
confidence: 99%
“…RCA is a key regulatory enzyme of photosynthetic carbon assimilation that modulates the activity of Rubisco by facilitating the removal of inhibiting sugar phosphates from its active site (Portis, 1995). Additional findings derived from the proteomic experimental approaches indicated that Rubisco large subunit and RCA, in addition to PS I P700 apoprotein A1 suffered several caterpillar-specific modifications, including the conversion of Cys192 in Rubisco to the the thiolate anion, which may lead to decreased enzyme activity and protein degradation, and adverse modifications, in RCA, of the protein domains involved in ATP binding (Thivierge et al, 2010).…”
Section: Main Photosynthetic Genes Targeted By Biotic Stressmentioning
confidence: 99%